Археологічні дослідження та популяризація давньоруських пам'яток у краєзнавстві Волинської області (1991–2016 рр.) - Пословська, А.; Карпюк, В. (Краєзнавство, 2019)
У статті простежено хід основних археологічних досліджень давньоруських пам'яток у Волинській області упродовж 1991–2016 рр. Узагальнено матеріали експедицій Волинського краєзнавчого музею, які працювали під керівництвом В.М. Коноплі, С.Д. Панишка, Ю.М. Мазурика та Любомльського краєзнавчого музею – під керівництвом О.Д. Остапюка та М.М. Кучинка. Підкреслено вагомий внесок в археологічне вивчення краю експедицій Львівського історичного музею, Луцького державного історико-культурного заповідника та Державного історико-культурного заповідника «Стародавній Володимир». Указано, що до вивчення археологічних пам'яток давньоруського періоду упродовж 1991–2016 рр. долучались викладачі та студенти історичного факультету (нині – факультету історії, політології та національної безпеки) Східноєвропейського національного університету імені Лесі Українки. Охарактеризовано активну археологічно-охоронну та дослідницьку роботу філії Інституту археології НАН України у Волинській області, що була створена в 1999 р., на базі якої згодом було сформоване ДП «Волинські старожитності». Окреслено результати основних експедицій, проведених упродовж 2002–2015 рр. У статті на матеріалах розкопок з'ясовано внесок окремих археологів у вивчення, популяризацію старожитностей регіону давньоруського періоду та розширення пізнавального потенціалу краєзнавства. The article traces the progress of basic archaeological studies of ancient memorials in the Volyn region during 1991–2016. It summarizes the materials of the expeditions of the Volyn Regional Museum, which worked under the direction of V.M. Konoplia, S.D. Panishko, Yu. M. Mazuryk. The materials of the expeditions of the Lyuboml Regional Museum under the guidance of O.D. Ostapyuk and M.M. Kuchinko are studied here. The article emphasizes on the significant contribution of the expeditions of the Lviv History Museum, Lutsk State Historical and Cultural Reserve and the State Historical and Cultural Reserve «Ancient Vladimir» to the archaeological study of the region. It states that the study of archaeological sites of the Ancient Russ period during 1991–2016 was attended by professors and students of the Faculty of History (now the Faculty of History, Political Science and National Security) of Lesya Ukrainka Eastern European National University. It describes the active archaeological-protective and research work of the branch of the Institute of Archeology of the NAS of Ukraine in Volyn region. This branch was established in 1999. On its basis, the SE «Volyn Antiquities» was formed later. The results of the main expeditions, carried out during the years 2002–2015, are outlined. Based on the excavation materials, the article clarifies the contribution of individual archaeologists to the study of antiquities of the region of the Ancient Russ period, popularization of these historical objects and extension of the cognitive potential of local history. The course and results of archaeological research in Volyn in 1991–2016 play a significant role in the study of the region. They indicate a significant amount of field work and expand the cognitive potential of local history. Thanks to archaeological research of this period, many new archaeological sources were introduced into scientific use. This allowed expanding the base of sources for studying the history of the region.